2x-1/3=x+5/5

Simple and best practice solution for 2x-1/3=x+5/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1/3=x+5/5 equation:



2x-1/3=x+5/5
We move all terms to the left:
2x-1/3-(x+5/5)=0
We add all the numbers together, and all the variables
2x-(x+1)-1/3=0
We get rid of parentheses
2x-x-1-1/3=0
We multiply all the terms by the denominator
2x*3-x*3-1-1*3=0
We add all the numbers together, and all the variables
2x*3-x*3-4=0
Wy multiply elements
6x-3x-4=0
We add all the numbers together, and all the variables
3x-4=0
We move all terms containing x to the left, all other terms to the right
3x=4
x=4/3
x=1+1/3

See similar equations:

| r/31=9 | | x+4x=-5+7x | | 12x+15=-33 | | h/9=-3 | | 4x+16x-5=4(5x+4) | | 2z-4/5=3z+3/10 | | 4(1-2x)=9 | | r+40=80 | | p+10/8=2p-7/4 | | 4(2x−1)−x−4=-1 | | 12.65b-3.75=9.45b-5.35 | | 18x+16-32=180 | | 4(2−x)+15=3(x+3) | | 2.m–8=6 2 | | f-65=14 | | 33.33333333333333333333333333333333x-2=x-6 | | h-7/4=2h+1/3 | | x/5=12. | | 4-2x=x+3 | | 9.68x+21.6-6.23=2.3+17 | | 1/3x-2=x-6 | | 13=k+46 | | 5−2p=3 | | 3x+5-3=4 | | 12y-3(y-3)=6y+8-(y-2) | | 2c-1/3=c+2/4 | | 12=s+70 | | t+11=89 | | j-5/2=j+8/7 | | 4.55m+6.25=7.55m+4.45 | | 5/7k+4=2/2k-3 | | 5(x+4)=3*2 |

Equations solver categories